2017
DOI: 10.1021/acs.jpcb.7b00035
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Vibrationally Driven Bimolecular Reactions in Solution: Reactions of Br Atoms with Dimethylsulfoxide and Methanol

Abstract: We present evidence for vibrational enhancement of the rate of bimolecular reactions of Br atoms with dimethylsulfoxide (DMSO) and methanol (CHOH) in the condensed phase. The abstraction of a hydrogen atom from either of these solvents by a Br atom is highly endoergic: 3269 cm for DMSO and 1416 or 4414 cm for CHOH, depending on the hydrogen atom abstracted. Thus, there is no thermal abstraction reaction at room temperature. Broadband electronic transient absorption shows that following photolysis of bromine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Collisions of chlorine atoms with neutral water clusters could potentially yield structures living long enough for observation, but these energy-dependent lifetimes are beyond the scope of the present analysis. A more promising prospect includes vibrational excitation, where past studies have driven this type of chemistry, including for chlorine–water complexes. ,, Overtone excitation of an O–H stretch, for example, would already yield enough energy to reach the entire manifold of HCl and charge-transferred structures. Nonetheless, the present computations have served to identify a series of new structures even at low energies, as well as determine the “lineage” of charge-separated species in much larger clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Collisions of chlorine atoms with neutral water clusters could potentially yield structures living long enough for observation, but these energy-dependent lifetimes are beyond the scope of the present analysis. A more promising prospect includes vibrational excitation, where past studies have driven this type of chemistry, including for chlorine–water complexes. ,, Overtone excitation of an O–H stretch, for example, would already yield enough energy to reach the entire manifold of HCl and charge-transferred structures. Nonetheless, the present computations have served to identify a series of new structures even at low energies, as well as determine the “lineage” of charge-separated species in much larger clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The dream of tuning light at a vibrational frequency of a particular bond and inducing a chemical reaction only at that site is extremely challenging, even using femtosecond pulses under low-pressure gas-phase conditions . This is partially because intramolecular vibrational energy redistribution (IVR) dissipates the deposited energy fast to other modes before the reaction arises. , Alternatively, if a dominant (nonstatistical) IVR pathway exists due to the coupling between an excited vibrational mode and a reaction coordinate, this might be exploited to induce a desired chemical transformation in an elegant and selective way. , One remarkable example illustrating this possibility is the vibrationally induced unimolecular reaction of the jet-cooled Criegee intermediate syn -CH 3 CHOO, reported by Lester and co-workers The authors demonstrated that excitation of CH stretching overtones or combination modes induces a 1,4-H shift from the methyl group to the terminal oxygen and activates decomposition of the molecule (Scheme ). Nevertheless, the application of this strategy to induce and control organic reactions remains scarcely explored. …”
mentioning
confidence: 99%
“…There has been evidence that atomic Br obtained via photolysis of Br 2 reacted with the solvent (dimethyl sulfoxide (DMSO) or methanol) in a vibrationally driven hydrogen abstraction to form HBr. Further, efforts were performed to use vibrational excitation to manipulate and initiate chemical reactions successfully. , In contrast to other attempts, we demonstrated the acceleration of a thermally driven reaction, namely the alcoholysis of urethane . The bimolecular synthesis reaction between CH-ol and PHI produces cyclohexyl-carbanilate in tetrahydrofuran (THF) solution (see Figure a), with an activation energy of ∼2340 cm –1 .…”
Section: Acceleration Of Ground State Reactions By Ir Light Absorptionmentioning
confidence: 82%
“…In contrast to reactions in the gas-phase , solute–solvent interactions potentially limit the prospects of laser-driven bond selective chemistry and reaction rate control by means of vibrational excitation. Hence only recently, the concept of reaction rate acceleration successfully used in gas phase bimolecular reactions has been implemented in solution . There has been evidence that atomic Br obtained via photolysis of Br 2 reacted with the solvent (dimethyl sulfoxide (DMSO) or methanol) in a vibrationally driven hydrogen abstraction to form HBr.…”
Section: Acceleration Of Ground State Reactions By Ir Light Absorptionmentioning
confidence: 99%